Intradiaphragmatic pulmonary sequestrations: a surgical challenge. Case series - Oreglio, Chiara; Tocchioni, Francesca; Ghionzoli, Marco; Buccoliero, Annamaria; Morabito, Antonino; Morini, Francesco (Frontiers in Surgery, 2023)
Bronchopulmonary sequestrations (BPSs) are rare congenital anomalies characterized by non-functioning embryonic lung tissue receiving anomalous blood supply. They are most commonly located within the thorax (supradiaphragmatic) or into the abdominal cavity (infradiaphragmatic). Intradiaphragmatic extralobar BPs (IDEPS) are an exceptionally rare finding, representing a diagnostic and operative challenge. We report three cases of IDEPS and their surgical management, describing our experience and approach to such rare clinical entities. From 2016 to 2022, we treated 3 cases of IDEPS. Surgical techniques, histopathological findings and clinical outcomes were retrospectively evaluated for each case and compared. 3 different surgical techniques were used to approach each lesion, from open thoracotomy to a combined laparoscopic and thoracoscopic approach. Histopathological analysis of the specimens revealed hybrid pathological features, proper of both congenital pulmonary airway malformation (CPAM) and extralobar pulmonary sequestration. IDEPS represent a surgical challenge for pediatric surgeons, given their complex surgical planning. In our experience, the thoracoscopic approach is safe and feasible when performed by trained surgeons, even though a combined thoracoscopic-laparoscopic approach allows for optimal vessels control. The presence of CPAM elements within the lesions supports their surgical removal. Additional studies are required to better characterize IDEPS and their management.